A study of the histopathological changes in heart in electrocution deaths - Dr. Shubha. H V; Dr. Nirmala. C (Tropical Journal of Pathology and Microbiology, 2018)
Introduction: One of the biggest challenges faced by forensic pathologists is death due to electrocution. In almost half of all cases no gross pathological findings can be seen. The history surrounding the cause of death and circumstantial evidence is sometimes ambiguous and possesses great difficulty.Aim: To study the various histopathological changes in heart in electrocution. Methods and materials: In the present study, a total of 15 heart specimens in electrocution deaths and 15 normal heart specimens are considered during the study period of one year from 2015 to 2016. Case details are obtained from the records and analyzed. The histopathological findings are recorded in a proforma.Results: Myofibre break-up, separation of sarcomeres and extravasation of RBCs are found in all the 15 cases of electrocution (100%). The other findings are disarray of the myofibres (87%), hyper contracted myocyte with squaring of nuclei (73%), myocellular segmentation (33%) and myocyte vacuolization (20%).Conclusion: The histopathological changes in heart definitely provide an additional clue in the diagnosis of electrocution deaths. Most of the histopathological changes in heart are found consistently in electrocution cases compared to that of the normal hearts. Hence, their presence can be relied upon in the diagnosis of electrocution deaths and in reducing the number of negative autopsies.